Superação de dormência e influência dos fatores ambientais na germinação de sementes de Spermacoce latifolia - Parreira, Mariana C. [UNESP]; Cardozo, Nilceu P. [UNESP]; Giancotti, Paulo R. F. [UNESP]; Da C. A. Alves, Pedro L. [UNESP] (Revista Brasileira de Ciencias Agrarias, 2011)
Understanding basic information on weed biology contributes to the implementation of appropriate management and control strategies. Thus, this work was developed to evaluate the germination of Spermacoce latifolia Aubl. seeds, an important weed in reforestation areas. The seeds were subjected to dormancy break treatments, in which the mechanical scarification, chemical treatment (H2SO 4 and KNO 3), heat treatment, and control, were evaluated. Three more tests were done determinate the effects of temperature (10, 15, 20, 25, 30 and 35°C), light filters (absence of light and red, green, yellow, distant red, blue, orange and clear light) and water availability (0.0, -0.2, -0.4, -0.6, -0.8 and -1.0 MPa) on the seeds germination and vigor. The treatments were arranged in a completely randomized design with four replications, and the experimental plot was constituted by gerbox plastic boxes with 50 seeds. The mechanical scarification (sanding) provided the best dormancy break, indicating that Spermacoce latifolia seeds have tegument water impermeability. The seeds showed higher germination percentage under conditions of mild water stress (-0.2 MPa) and the optimal temperature was 25°C. The blue light reduced seed germination.
Dormancy break and influence of environmental factors on the germination of Spermacoce latifolia seeds
Keywords: Light quality; Scarification; Temperature; Water availability; Spermacoce latifolia